Heart failure in Fabry disease revisited: application of current heart failure guidelines and recommendations. (29th August 2022) - Rob, Daniel; Marek, Josef; Dostalova, Gabriela; Linhart, Ales
Abstract: Aims: Fabry disease (FD) is often associated with heart failure (HF). However, data on HF prevalence, prognosis, and applicability of echocardiographic criteria for HF diagnosis in FD remain uncertain. Methods and results: We evaluated patients with genetically proven FD for symptoms and natriuretic peptides indicating HF. We then analysed the diagnostic utility of the currently recommended European Society of Cardiology (ESC) echocardiographic criteria for HF diagnosis and their relationship to natriuretic peptides. Finally, we examined the association between HF and echocardiographic criteria with mortality and cardiovascular events during follow‐up. Of 116 patients with FD, 48 (41%) had symptomatic HF (mean age 58 ± 11 years, 62% male). HF with preserved ejection fraction (HF‐pEF) was diagnosed in 43 (91%) patients, representing the dominant phenotype. Left ventricular mass index (LVMi) had the highest diagnostic utility (sensitivity 71% and specificity 83%) for HF diagnosis in FD, followed by E/e′ > 9 (sensitivity 76% and specificity 78%) and global longitudinal strain (GLS) <16% (sensitivity 54% and specificity 88%). Log N‐terminal pro‐brain natriuretic peptide correlated significantly with LVMi ( r = 0.60), E/e′ ( r = 0.54), and GLS ( r = 0.52) (all P s < 0.001) but not with left ventricular ejection fraction ( r = −0.034, P = 0.72). During follow‐up (mean 1208 ± 444 days), patients diagnosed with HF had a higher rate of all‐cause mortality and worsening HF (33% vs. 1.5%, P < 0.001). Abnormal LVMi, E/e′ > 9, and GLS < 16% were all associated with higher all‐cause mortality and worsening HF. Conclusions: This study found a high prevalence of symptomatic HF in FD patients. HF‐pEF was the dominant phenotype. LVMi, E/e′, and GLS yielded the highest diagnostic utility for HF diagnosis and were significantly correlated with natriuretic peptides levels. Echocardiographic criteria proposed by current ESC HF guidelines apply to Fabry patients and predict cardiovascular events. At follow‐up, Fabry patients with HF diagnosis had high event rates and significantly worse prognosis than patients without HF.